Mirror of His beauty : feminine images of God from the Bible to the early Kabbalah - Schäfer, Peter, 1943- (Princeton : Princeton University Press, 2002)
"In this beautifully realized study, Peter Schafer investigates the origins of a female manifestation of God in Jewish mysticism. The search itself is a fascinating exploration of the idea of a feminine divinity. And Schafer's surprising but persuasive conclusions yield deeper understanding of the complex but frequently intimate relationship between Christianity and Judaism - and of the development of religious concepts more generally. Toward the end of the twelfth century, a small book titled the Bahir (Light) appeared in Provence. The first document of Judaism's emerging kabbalistic movement, it introduced a completely new view of God, one that included a divine potency that was essentially female. This female divinity was portrayed both as a mediator between Jews and God and as part of the Godhead itself. Examining Judaic history from the biblical Wisdom tradition to the Middle Ages, Schafer finds some precedents for the Kabbalah's feminine divinity. But he cannot account for her forceful appearance in twelfth-century southern France without reference to the immediate Christian environment, particularly the flourishing veneration of the Virgin Mary. Indeed, twelfth-century Jews and Christians were simultaneously rediscovering the feminine as an aspect of the Godhead after having abandoned it in favor of either an abstract, disembodied God or an exclusively male one. In proposing that the medieval cult of Mary - rather than eastern Gnosticism - is the appropriate framework for understanding the feminine elements in Jewish mysticism, Mirror of His Beauty represents a sea change in Kabbalah and Jewish-Christian cultural studies. It shifts our attention from the Byzantine East to the Latin Christian West. And in contrast to histories that treat the development of Judaism and Christianity in isolation, it leads us to a fuller understanding of Jews and Christians living in proximity, aware of each other."--Publisher's description
From the Bible to the Bahir -- Lady Wisdom -- Job: Wisdom Cannot Be Found -- Proverbs: Wisdom as God's Little Daughter and His Embodiment on Earth -- Jesus Sirach: Wisdom as God's Torah -- Wisdom of Solomon: Wisdom as the Medium of Divine Energy and God's Beloved Spouse -- Philo's Wisdom -- God and His Wisdom -- Wisdom and Logos -- Wisdom's Gender -- God's Daughter -- Divine and Human Wisdom -- Summary--and Once Again Gender -- The Gnostic Drama -- The Creation Myth According to the Apocryphon of John -- Barbelo -- The Self-Generated/Christ -- Sophia and Her Offspring -- Sophia's Descent -- Sophia and Barbelo -- The Valentinian Creation Myth According to Irenaeus -- Passionate Sophia -- Sophia and Achamoth, Upper and Lower Wisdom -- The Rabbinic Shekhinah -- Wisdom -- God the Only Creator -- Israel, God's Spouse, Daughter, Sister, and Mother -- Shekhinah -- Personification of the Shekhinah -- The Shekhinah of the Philosophers -- Saadia Gaon -- Judah ben Barzillai of Barcelona -- Judah ha-Levi -- Moses Maimonides -- The Shekhinah in the Bahir -- The Ten Sefirot -- Sexual Symbolism -- The Position of the Shekhinah in the Sefirotic System -- Mediatrix between Heaven and Earth -- The Quest for Origins -- Gnosis -- Christianity -- Eastern Church -- Western Church -- Peter Damian -- Herman of Tournay -- Bernard of Clairvaux -- Godfrey of Admont -- Hildegard of Bingen -- Peter of Blois -- Mary and the Shekhinah -- Counter-Evidence: Mary and the Jews -- Anti-Jewish Legends and Images -- The Jews Disturb Mary's Funeral.
Includes bibliographical references (pages 289-300) and index.
Description based on online resource; title from digital title page (viewed on March 01, 2023).
JSTOR
Keywords: Bibel; Femininity of God -- History of doctrines; Femininity of God -- Biblical teaching; Cabala; Dieu -- Féminité -- Histoire des doctrines; Dieu -- Féminité -- Enseignement biblique; Kabbale; RELIGION -- Comparative Religion; Cabala; Femininity of God -- Biblical teaching; Femininity of God -- History of doctrines; Christentum; Feministische Theologie; Judentum; Godsvoorstellingen; Vrouwelijkheid; Oude Testament; Jodendom